Green Chemistry Education In The Emerging Economies In Asia - Jovero, M. B.; Picardal, J. P. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2022)
This paper aims to investigate and synthesize literature exploring the current state of Green Chemistry Education (GCE) in the emerging economies in Asia to determine what has been done and the continuing projects for the promotion of Green Chemistry (GC). The researchers used the integrative literature review approach to examine qualitative, quantitative, and mixed methods and empirical and theoretical literature related to GCE. This approach includes (a) problem identification, (b) search for structured literature, (c) data evaluation, (d) data analysis, and (e) presentation of findings. Published studies revealed that most initiatives in integrating GC principles in emerging economies in Asia focused on the secondary and tertiary levels but not graduate studies and non-chemistry-related courses. Most of its progress has been observed in Organic Chemistry and General Chemistry. Results also revealed that the barriers that hampered integrating GCE are pedagogical resources (insufficient or unavailability of time, financial and technological resources) and pedagogical content knowledge (misconceptions about GC, lack of expertise, and the need to update technical knowledge). It can be concluded that even in the initial stage of implementation of green chemistry education in the emerging economies in Asia, and despite numerous documented barriers, proactive efforts are being made by numerous institutions and even individuals who are tenaciously advocating green chemistry. These efforts are enriched through various educational programs, learner-centered pedagogical practices, and strategies that enhance teachers’ and students’ content knowledge and skills. Finally, economics is a major factor in determining a country’s state of Green Chemistry as the economic condition can be credited to outstanding or dismal achievements.